ANALYSIS OF TEACHER READINESS IN APPLYING THE 2013 CURRICULUM IN THE IV GRADE OF PRIMARY SCHOOL - Saibaton Saibaton; Mardhatillah Mardhatillah (Teunuleh Publisher, 2020)
This study aims to analyze how readiness the teachers are in implementing the 2013 curriculum at SD Negeri Peureumeu, Kaway XVI District. The research approach used in this research is qualitative research. This type of research is descriptive (descriptive research). The subjects in this study were 8 teachers in Peureumeu Public Elementary School, Kaway XVI sub-district, and 1 grade IV teacher was studied. Data collection methods in this research are observation, interview, documentation and validation. The conclusion of this research is that in implementing the 2013 curriculum, the fourth-grade teachers at Peureumeu Public Elementary School, Kaway XVI District are very ready to implement the 2013 curriculum. The main readiness carried out by grade IV teachers at SD Negeri Peureumeu, Kaway XVI District in implementing the 2013 curriculum is the process of learning, by designing or designing specifically the learning material with reference to the syllabus and lesson plans. The second is the readiness of the classroom management aspects, the three readiness methods, the fourth readiness for the use of teacher books and student books, and the last is the readiness of the assessment process, the teacher is able to use the results of the assessment analysis in the learning process, and the teacher evaluates the effectiveness of the process and learning outcomes and uses information on results assessment and evaluation to design remedial and enrichment programs.